Avaliação do potencial fungicida e termiticida de uma fração protéica lectínica de sementes de Platypodium elegans Vogel e obtenção da lectina purificada - Benevides, Raquel Guimarães (2008)
Seeds of Platypodium elegans Vogel, belonging to the Fabaceae family, Papilionoideae sub-family, Dalbergiae Tribe, posses a specific mannose/glucose lectin. In the purification of the lectin in study, the total extract of seeds of P. elegans prepared in NaCl 0,15M had its active fraction isolated for affinity chromatography in chitin and exchange ionic chromatography in DEAE-Sephacel and HiTrap SP, this last one connected to the HPLC.The active fractions for hemmagutinant activity gotten in these procedures had been sequentially about its specific activity and homogeneity in SDS-PAGE. The lectin in the last step of purification presented apparent molecular mass of 55 kDa. The active fraction from DEAE-Sephacel was characterized about its termiticidal and fungicidal potential. The termiticidal activity against laborers and soldiers of Nasutitermes corniger, inducing 100% of mortality in both the classrooms, was better visualized with the concentrations of 1,0 and 0,8mg/mL, between 8 and 9 days for laborers and 7 and 8 days for soldiers, where it had not been registered mortality less than 50% in the negative control. The tested fraction did not present repellent effect. In relation to the fungicidal activity, 20 ug of the fraction arrived to inhibit considerably Fusarium lateritium (33%), F. oxysporum (19.4%) and F. solani (14.3%). F. decemcellulare had a inhibition of 4,8% and F. moniliforme, 3.3%. These two activities strengthen the participation of this lectin in the vegetal defense, making it a powerful biotechnological tool to be more deeply investigated and studied about its paper in the vegetal defense and the potential use in the resistance of susceptible wood to termites.